Indigeneity, Culture and the UN Sustainable Development Goals - O’Sullivan, Dominic. author. aut Link
XIV, 277 p. 1 illus.
Keywords: “A robust, well-theorised, and incisive critique that exposes the inattention of the Sustainable Development Goals (SDGs) to the histories, legacies, voices, aspirations, and authority of Indigenous peoples. A timely contribution to contemporary debates on nationhood, sovereignty, Indigenous recognition, and social justice.” ---Professor Tanya Fitzgerald, The University of Western Australia, Australia “Asserting that Indigenous self-determination is ‘colonialism’s antithesis’, O’Sullivan navigates the interconnected relationships between culture, self-determination, and sustainable development, affirming that continued policy failure in indigenous affairs is not inevitable.” ---Dr Jessa Rogers, Queensland University of Technology, Australia "A leader in indigenous political theory, O'Sullivan produces a series of arguments that wrench the UN's Sustainable Development Goals from their non-indigenous biases, in order to preserve the hope that they might serve the whole of humanity. A formidable work of indigenous political theory from one of this emerging discipline's foremost scholars." ---Dr Lindsey MacDonald, University of Canterbury, New Zealand This is the first scholarly book to examine the UN Sustainable Development Goals from an indigenous perspective. It refers to the UN Declaration on the Rights of Indigenous Peoples and domestic instruments such as New Zealand’s Tiriti o Waitangi to suggest how the goals could be revised to support self-determination as a more far-reaching and ambitious project than the goals currently imagine. The book draws on Australian, Canadian, and New Zealand experiences to analyse the goals’ policy relevance to wealthy states and indigenous rights in established liberal democracies. Dominic O’Sullivan is Professor of Political Science at Charles Sturt University, Adjunct Professor at the Auckland University of Technology and Academic Associate at the University of Auckland. He is from the Te Rarawa and Ngati Kahu iwi of New Zealand, and this is his ninth book. The most recent, Sharing the Sovereign: Indigenous Peoples, Recognition, Treaties and the State was published by Palgrave in 2021.